Konsep Pembentukan Karakter Siddiq dan Amanah pada Anak melalui Pembiasaan Puasa Sunat - Saifullah Saifullah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
The planting of siddiq and amanah characters should begin as a child. Because the child is a white paper that will be something in accordance with what he learned since childhood. When fasting, the child is trained to really be a good human being who should not be tied to the slightest sin. This is what then form the character of shiddiq and amanah in children. Fasting circumcision is a worship that is able to form a character of siddiq then the child will have a trustful character. This is due to fasting circumcision in the same implementation with the fasting of Ramadan. When the child has received a command and tried to practice it, it will be born the character of trust and responsibility to the child.